Dadas as funções f(x) = -x2 +7x -10 e g(x) x2 -5x +12, calcule g (f (-3))
Soluções para a tarefa
Respondido por
1
Olá,
Primeiro devemos calcular f(-3).
f(x) = -x² + 7x - 10
f(-3) = -(-3)² + 7*(-3) - 10
f(-3) = - 9 - 21 - 10
f(-3) = - 40
Agora, podemos calcular a g(f(-3)) = g(-40)
g(x) = x² - 5x + 12
g(-40) = (-40)² - 5*(-40) + 12
g(-40) = 1600 + 200 + 12
g(-40) = 1812
Bons estudos ;)
Primeiro devemos calcular f(-3).
f(x) = -x² + 7x - 10
f(-3) = -(-3)² + 7*(-3) - 10
f(-3) = - 9 - 21 - 10
f(-3) = - 40
Agora, podemos calcular a g(f(-3)) = g(-40)
g(x) = x² - 5x + 12
g(-40) = (-40)² - 5*(-40) + 12
g(-40) = 1600 + 200 + 12
g(-40) = 1812
Bons estudos ;)
Perguntas interessantes
Matemática,
10 meses atrás
Sociologia,
10 meses atrás
História,
10 meses atrás
Matemática,
1 ano atrás